2020
DOI: 10.3390/nano10091642
|View full text |Cite
|
Sign up to set email alerts
|

The Magnetic Proximity Effect Induced Large Valley Splitting in 2D InSe/FeI2 Heterostructures

Abstract: The manipulation of valley splitting has potential applications in valleytronics, which lacks in pristine two-dimensional (2D) InSe. Here, we demonstrate that valley physics in InSe can be activated via the magnetic proximity effect exerted by ferromagnetic FeI2 substrate with spin-orbit coupling. The valley splitting energy can reach 48 meV, corresponding to a magnetic exchange field of ~800 T. The system also presents magnetic anisotropy behavior with its easy magnetization axis tunable from in-plane to out-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Valley information has emerged as an information carrier to store, process and compile information, which has the advantages of high-speed and low-power consumption 173 with respect to charge carriers in traditional semiconductor technology. 174 The manipulation of the degrees of valley freedom has been demonstrated, and a field called valley electronics, or valleytronics, is springing up. As a star family of 2D materials, most transition metal chalcogenides (TMCs) exhibit degenerate valleys owing to the protection of time-reversal symmetry, which is unsuitable for information storage.…”
Section: Spintronic Devices Based On 2d Fe3x(x=ge and Ga)te2 Van Der ...mentioning
confidence: 99%
“…Valley information has emerged as an information carrier to store, process and compile information, which has the advantages of high-speed and low-power consumption 173 with respect to charge carriers in traditional semiconductor technology. 174 The manipulation of the degrees of valley freedom has been demonstrated, and a field called valley electronics, or valleytronics, is springing up. As a star family of 2D materials, most transition metal chalcogenides (TMCs) exhibit degenerate valleys owing to the protection of time-reversal symmetry, which is unsuitable for information storage.…”
Section: Spintronic Devices Based On 2d Fe3x(x=ge and Ga)te2 Van Der ...mentioning
confidence: 99%
“…Breaking the time inversion symmetry by introducing magnetic exchange field can generate valley polarization. The usual methods for introducing magnetic exchange fields include magnetic proximity effect [29][30][31][32][33][34][35][36][37][38][39][40], magnetic atom doping [41][42][43][44][45][46][47], and applying external magnetic field [48][49][50][51]. When the time reversal symmetry is broken and the spin-orbit coupling (SOC) is considered, valley splitting will occur at the high symmetric points K and K ′ , leading to valley polarization.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that vdWHs could exhibit various interesting electronic, optical, , and magnetic , features. Furthermore, they can be effectively modulated by electrical, mechanical, , and optical , means. The multifunctionality and high tunability of vdWHs increase the applicability of 2D materials in nanodevices, for example, photodetectors, transistors, , and spintronic devices. ,, …”
Section: Introductionmentioning
confidence: 99%